Aid Organisations and Prison Ministry in Communist Poland and Their Role in the Resocialisation of Prisoners after 1980 - Kudlak, Grzegorz; Zimny, Mateusz (Acta Poloniae Historica, 2019)
This article traces the history of penitentiary and post-penitentiary practices by churches (primarily Catholic) and social aid organizations in Poland. The involvement of churches and social organizations in prisoner assistance began, partly underground, during the period of the Polish partitions, and took on formal roles and structures during the Second Republic of Poland (1918–39). However, beginning with the Second World War and until the year 1980 the earlier practice of ministry in prisons was significantly limited. The Nazi and Soviet hostile attitude towards religion was continued and in some ways exacerbated during the period of communist governments in Poland, when the function of prison chaplain as well as prison chapels themselves were liquidated, and all that officially remained of the conduct of religious services in prisons was the administration of last sacraments to prisoners about to be executed or terminally ill. During this period the church’s support for prisoners was mostly limited to that offered by clergymen who were themselves inmates. The role of prison ministry and social aid organisations in both penitentiary and post-penitentiary work was revived following the strikes, and consequent mass arrests, which took place in August 1980. The new scope and dimension of prison ministry began with the re-instatement of the function of prison chaplain and has evolved in recent decades to the point where today prison chaplains and church ministries, working alongside non-governmental aid organizations, have become an indispensable part of both the administration of prisons as well as post-penitentiary supervision and assistance.